Differential expression of efflux pump genes of Mycobacterium tuberculosis in response to varied subinhibitory concentrations of antituberculosis agents. Issue 2 (March 2015) - Garima, Kushal; Pathak, Rakesh; Tandon, Rashmi; Rathor, Nisha; Sinha, Rajesh; Bose, Mridula; Varma-Basil, Mandira
Summary Several reports have elaborated on the role of efflux pumps in drug resistance in Mycobacterium tuberculosis by analysing the mRNA expression profiles. However, there is no uniformity in the subinhibitory concentrations of drugs chosen in these studies. Some investigators studied the expression of efflux pumps under a drug concentration of 1/2 minimum inhibitory concentration (MIC), while others used 1/3, 1/4 or 1/8MIC. The present study was planned to understand the effect of different concentrations of antituberculosis drugs on the expression of efflux pump genes. Log phase culture of the laboratory strain M. tuberculosis H37Rv was exposed to rifampicin (RIF), isoniazid (INH), streptomycin (SM) and ethambutol (EMB) at different drug concentrations (1/2MIC, 1/3MIC and 1/4MIC). The expression of 10 putative efflux pump genes was studied using quantitative Real Time-Polymerase Chain Reaction (qRT-PCR). We observed an optimal expression of efflux pumps at higher concentrations of INH; and at lower concentrations of RIF and EMB. However, in the presence of SM, a decreased expression of efflux genes with increasing concentrations of the drug was confounded by a significant reduction in Colony Forming Units (CFU).